2021
DOI: 10.1098/rsos.210626
|View full text |Cite
|
Sign up to set email alerts
|

The hydroperoxyl radical scavenging activity of sulfuretin: insights from theory

Abstract: Sulfuretin (SFR), which is isolated from Rhus verniciflua , Toxicodendron vernicifluum, Dahlia, Bidens tripartite and Dipterx lacunifera , is one of the most important natural flavonoids. This compound is known to have numerous biological activities; among these, the antioxidant activity has not been thoroughly studied yet. In this study, the hydroperoxyl scavenging activity of SFR was examined by using dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…According to this data, 7OGT has lower BDE(O−H) values than e.g. vanillic acid (85.2 kcal mol −1 ), [16] puerarin (87.3 kcal mol −1 ), [54] resveratrol (83.9 kcal mol −1 ), [55] or viniferifuran (82.7 kcal mol −1 ) [56]. This suggests that 7OGT could exhibit faster antiradical activity (following the FHT mechanism) than these natural antioxidants.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…According to this data, 7OGT has lower BDE(O−H) values than e.g. vanillic acid (85.2 kcal mol −1 ), [16] puerarin (87.3 kcal mol −1 ), [54] resveratrol (83.9 kcal mol −1 ), [55] or viniferifuran (82.7 kcal mol −1 ) [56]. This suggests that 7OGT could exhibit faster antiradical activity (following the FHT mechanism) than these natural antioxidants.…”
Section: Resultsmentioning
confidence: 98%
“…Thermodynamic evaluation in pentyl ethanoate and water (electronic supplementary material, table S2) did not differ at the most likely site of activity (BDE = 74.6 and 78.9 kcal mol −1 and Δ G ° = −10.7 and −9.6 kcal mol −1 in the lipid and water media, respectively) for the neutral state (H 2 A), however, the PL and SET pathways of this state are not spontaneous in either media (Δ G ° > 0). Previous studies showed that for a compound containing acidic moieties the SET reaction of the dissociated states should be also considered in the aqueous solution [16,18,21,37,54,57]. Thus, the kinetics of the radical scavenging activity of 7OGT against HOO • radical in physiological media were carried out following equations (3.1) and (3.2) below, and the results are presented in table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometry optimization and frequency calculation were carried out with the package of programs Gaussian 09, [36] employing the functional M06-2X and the basis-set 6-31G(d,p), employing the solvent model of continuum density (SDM) [37] with pentyl ethanoate as a solvent to mimic the lipid media. [38][39][40] The M06-2X is among the best performing functionals for calculating reaction energies involving free radicals and for kinetic calculations in solutions. [41,42] The geometry optimization and frequency calculations from the first singlet excited-state ( 1 CUR*) employed TD-DFT calculations, including the solvent effects, in the TD-M06-2X/6-31G(d,p) level.…”
Section: Experimental Methods and Computational Detailsmentioning
confidence: 99%